2014
DOI: 10.1007/s10948-014-2689-7
|View full text |Cite
|
Sign up to set email alerts
|

Increase in T c and Change of Crystal Structure by High-Pressure Annealing in BiS2-Based Superconductor CeO0.3 F 0.7BiS2

Abstract: Recently, several types of BiS 2 -based superconductor such as Bi 4 O 4 S 3 , REO 1-x F x BiS 2 (RE: rare earth) and Sr 1-x La x FBiS 2 have been discovered. In this study, we have investigated the crystal structure and the superconducting properties for two kinds of polycrystalline samples (As-grown and high-pressure-annealed samples) of the BiS 2 -based superconductor CeO 0.3 F 0.7 BiS 2 . We found that both the As-grown and the high-pressure-annealed CeO 0.3 F 0.7 BiS 2 samples show bulk superconductivity. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 21 publications
(35 reference statements)
2
16
0
Order By: Relevance
“…2) has been reported for Bi 4 O 4 S 3 [55], which might suggest that the larger bending of the Bi-S-Bi bond is responsible for superconductivity. A similar distortion of the Bi-S layers 125 in LaO 1−x F x BiS 2 , CeO 1−x F x BiS 2 , and PrO 0.5 F 0.5 BiS 2 has also been observed [36,37,56,46]; the distortion of the Bi-S layers could be attributed to a fully occupied Bi s-orbital. Chemical substitution of F for O is considered to induce charge carriers into the Bi-S layer, and this is believed to induce supercon-130 ductivity in the mixed-anion layered compounds LnO 1−x F x BiS 2 (Ln = La, Ce, Pr, Nd, Yb) [6,36,8,37,15,38,39,40,41,42].…”
Section: Introductionsupporting
confidence: 59%
“…2) has been reported for Bi 4 O 4 S 3 [55], which might suggest that the larger bending of the Bi-S-Bi bond is responsible for superconductivity. A similar distortion of the Bi-S layers 125 in LaO 1−x F x BiS 2 , CeO 1−x F x BiS 2 , and PrO 0.5 F 0.5 BiS 2 has also been observed [36,37,56,46]; the distortion of the Bi-S layers could be attributed to a fully occupied Bi s-orbital. Chemical substitution of F for O is considered to induce charge carriers into the Bi-S layer, and this is believed to induce supercon-130 ductivity in the mixed-anion layered compounds LnO 1−x F x BiS 2 (Ln = La, Ce, Pr, Nd, Yb) [6,36,8,37,15,38,39,40,41,42].…”
Section: Introductionsupporting
confidence: 59%
“…4(b) and (d) the diamagnetic response is clearly seen in the virgin low field region (from which H c1 is easily estimated to be ~44 Oe and 40 Oe for x  = 0.5 and 1.0 respectively. It is important to point out that in the selenium-free compound Sr 0.5 Ce 0.5 FBiS 2 ( T c  ~ 2.6 K & T FM  ~ 7.5 K)2744 and in a similar material Ce(O, F)BiS 2 ( T c  ~ 2.5–4 K & T FM  ~ 6.5–7.5 K)20525367 no superconducting hysteresis loop was observed. This is consistent with our own results on Sr 0.5 Ce 0.5 FBiS 2 (inset of Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The compositional ratio was determined to be La:Bi:S = 1:0.99:1.72, by normalizing La = 1 in the EDX analysis, which is consistent with the cation composition of La(O,F)BiS2. The single crystal XRD analysis revealed that the compound crystallizes with a tetragonal structure, with typical lattice constants of a = 4.0541 (15) Å and c = 13.4826(52) Å. The EDX and XRD analyses establish that the obtained products are La(O,F)BiS2 single crystals.…”
mentioning
confidence: 83%